2013
DOI: 10.1111/deve.12002
|View full text |Cite
|
Sign up to set email alerts
|

How Does Country Risk Matter for Foreign Direct Investment?

Abstract: Using the overall FDI inflows for 89 countries during the period from 1985 to 2007, we empirically investigate the effects on inward FDI of various components of political and financial risk. We examine the effects of not only the level of these risks but also their changes over time. One of the major findings is that among the political and financial risks, only the political risk is adversely associated with FDI inflows. Specifically, not only the initially low level of political risk, but also a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 18 publications
(16 reference statements)
4
85
1
6
Order By: Relevance
“…It indicates that the external position of the economy is good which increases the investor confidence. Hayakawa, Kimura and Lee (2011) found an insignificant impact of financial risk on FDI flows for a panel of 93 countries.…”
Section: Credit Worthinessmentioning
confidence: 95%
“…It indicates that the external position of the economy is good which increases the investor confidence. Hayakawa, Kimura and Lee (2011) found an insignificant impact of financial risk on FDI flows for a panel of 93 countries.…”
Section: Credit Worthinessmentioning
confidence: 95%
“…Most studies indicate that political stability may have a positive effect on the incoming FDI (Busse & Hefeker, 2007;Hayakawa, Kimura, & Lee, 2011;Wei, 2000). Also, the high sunk cost of FDI is associated with uncertainties, including the political uncertainty, and makes investors highly sensitive in their investment decisions (Walsh & Yu, 2010).…”
Section: A Panel Data Analysis 150mentioning
confidence: 99%
“…The author concluded that political risk is unrelated to ROA of the companies. Hayakawa et al (2011) examined the impact of various components of political as well as financial risk on inward FDI, from both long-and short-run perspectives, using risk indices from PRS. The paper employs the dynamic Generalized Method of Moments (GMM) estimator with data from 90 countries for the period 1985-2007 and focused most of their findings on developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%